Performing Demand Management Strategy on Palm Sugar Supply Chain in Kutai Kartanegara Regency’s Commodities - Astuti Wisudayati Tri; Charity Hidayat Dian (E3S Web of Conferences, 2023)
Unfortunately, there are unsolved critical issues of demand in a palm sugar supply chain, such as a propensity for the mismatch of demand and supply due to no local livelihood sustainability, inconsistency in handling palm sugar quality, and inappropriate institutional mechanisms. Highlighting the problems and proposing demonstrated “demand management”, this research draws on empirical evidence from case studies. The case study evidence based on the conceptual framework is drawn exclusively from Tuana Toha Village, in the Peatland Hydrological Unit area in Kutai Kartanegara Regency, where palm sugar potential is generally more mature than in other districts of Kutai Kertanegara Regency. So, this research objective proposes a comprehensive instrument of “demand management” for stabilizing the palm sugar supply chain through the improvement framework for the demand management process. The research method by participatory observation involves researchers actively participating to understand better the role and activities of micro-enterprises/ local communities in the development of palm sugar. This method can help identify problems and challenges that may not see through other research methods. Establishing four stages in the improvement framework for the demand management process: stage of definition, distribution, diagnosis, and execution. This research’s essential results state that collaboration, information sharing, and cooperatives are instruments to meet supply and demand efficiently.